2020
DOI: 10.1159/000507078
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Symptoms in Mild Cognitive Impairment: A Literature Review

Abstract: Background: Neuropsychiatric symptoms (NPS) in dementia have received much attention due to their high prevalence and their significant implications. NPS in mild cognitive impairment (MCI), a clinical concept proposed as an intermediate state between normal aging and dementia, is now gradually gaining in interest. We aimed to conduct a selective review to examine the prevalence rate of NPS in MCI and associations of NPS symptoms with disease progression. Summary: We searched the PubMed database for articles on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 59 publications
(107 reference statements)
4
79
0
Order By: Relevance
“…In the present study, patients with a history of hallucination, anxiety, and memory deficits were more likely to receive a diagnosis of AD. Some of these symptoms together with the presence of cognitive deficits may be framed in the context of mild cognitive impairment construct, which can be an early clinical manifestation of prodromal dementia [16, 17]. In this regard, the lack of indications and guidelines for the assessment of cognitive impairment in primary care weakens the possibility for GPs to perform timely diagnosis and appropriately refer patients to dedicate second level services.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, patients with a history of hallucination, anxiety, and memory deficits were more likely to receive a diagnosis of AD. Some of these symptoms together with the presence of cognitive deficits may be framed in the context of mild cognitive impairment construct, which can be an early clinical manifestation of prodromal dementia [16, 17]. In this regard, the lack of indications and guidelines for the assessment of cognitive impairment in primary care weakens the possibility for GPs to perform timely diagnosis and appropriately refer patients to dedicate second level services.…”
Section: Discussionmentioning
confidence: 99%
“…Little research conceptualized NPS as a complex of symptoms. Increasing evidence indicates that NPS usually manifest as a cluster of behavioral and psychological symptoms of various combinations, severities and frequencies, even the earlier disease stage 15,79,80 . Given this, the European Alzheimer's Disease Consortium published a consensus review paper, which recommended that the evaluation of an intervention's efficacy should focus on its effects on overall NPS rather than a single domain 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Of these seven studies, five 60,65,67,72,74 reported significant treatment effects, whereas the remaining two 59,71 did not. Table 2 15,79,80 Given this, the European Alzheimer's Disease…”
Section: Crucial Components Of Effective Interventionsmentioning
confidence: 99%
“…The absence of dementia or of mild cognitive impairment will not be good enough for a task which needs permanent mental and physical strength over long periods of time. Some of the following features may serve as markers of im-minent cognitive failure and help to identify candidates at risk: the statistical risk which comes with very old age; a record of failures and how they were dealt with; signs of physical frailty and the kind of multimorbidity which may impact on endurance and cognitive capacity in due course; impaired fluency or limited communicative content, rambling style, ideological phrases instead of focused pragmatism [25]; unsubstantiated pride relying on previous achievements; mild behavioral impairment [26]; tiring easily, memory lapses; mild cognitive impairment; supportseeking gestures [27]; a tightly knitted and manipulative entourage pursuing their own interests. This is not an attempt to rewrite political history as a history of senility or a general warning against candidates over the age of 65.…”
Section: Discussionmentioning
confidence: 99%